Assessment of physical activity level among patients with type 2 diabetes mellitus attending rural health centre, Marappadi - Bruce, M. S. Praythiesh; Mallika, M. C. Vasantha (International Journal Of Community Medicine And Public Health, 2019)
Background: Insufficient physical activity is one of the ten leading risk factors for death among patients with Non- Communicable Diseases (NCDs) such as cardiovascular diseases, cancer, and diabetes mellitus worldwide. Globally, one in four adults is not physically active. More than 80% of the world’s adolescent population is insufficiently physically active. Physical inactivity is very common in India with a prevalence of 54.4%. Lack of knowledge regarding physical activity leads to non-communicable diseases (NCDs) such as cardiovascular diseases, cancer, and diabetes which in turn can lead to death and disability. Methods: The cross sectional study was conducted on patients diagnosed to be diabetic visiting the Out Patient Department of Rural Health Centre Marappadi. Convenient sampling was used and the study was conducted from January 2017 to June 2018 using a pre-tested, semi-structured questionnaire. Results: The mean age of the patients was 57.00±8.747 years. Patients aged 60 years and above had a lower physical activity level. In the older age group, low physical activity was associated with obesity. Adequate motivation was found to be reason for high physical activity level in patients (60.0%). Conclusions: The physical activity levels of the diabetic patients were unsatisfactory especially in the elderly. Low physical activity was associated with poor glycaemic control in the older age group. There is a need to encourage diabetic patients to undertake regular physical activity in order to achieve good health and well-being, optimal glycaemic control and to prevent diabetic complications.